Zirconium oxide powder for multi-component composite doped solid fuel cell and preparation method of zirconium oxide powder
By optimizing the composite doping system and calcining process of zirconia powder, a multivariate composite doped zirconia powder was prepared, which solved the volume change problem caused by phase change of zirconia powder at high temperature, and achieved nano zirconia powder with high oxygen ionic conductivity and high temperature stability, meeting the high performance needs of solid fuel cell electrolytes.
Patent Information
- Application Number
- CN202510062470.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-18
AI Technical Summary
In existing solid fuel cells, zirconia powders have volume changes due to the martensite phase change, making it difficult to make a dense film, and a single doped oxide has limited performance improvement.
By optimizing the type, dosage and calcination process of the composite doped oxide system of zirconia powder, a multivariate composite doping system is adopted, including scandium as the main stabilizer and cerium salt, aluminum salt, bismuth salt, and gadolinium salt as composite additives, and nanozirconia powder is prepared through the modification of carbon nanotubes and organic frames, combined with a two-step calcination process.
The prepared multi-component doped zirconia powder has high oxygen ion conductivity and excellent high temperature stability. It can meet the high performance needs of a variety of solid fuel cell electrolytes and has good market competitiveness.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid fuel cells, and in particular relates to a multi-component composite doped zirconium oxide powder for solid fuel cells and a preparation method thereof. Background Art
[0002] The electrolyte of a solid fuel cell is a solid, void-free metal oxide, in which oxygen ions shuttle through the crystal to deliver ions; because its entire power generation process is an electrochemical reaction, it does not require fuel combustion, so there is no limitation of the Carnot cycle, and the theoretical conversion efficiency can reach more than 85%-90%. Compared with other fuel cells, solid fuel cells also have the advantages of high power density, strong fuel adaptability, all-solid-state structure, and simple equipment. Zirconia has excellent ionic conductivity and resistance to high-temperature aging, and can maintain a high ion conduction efficiency at high temperatures, making it the preferred material for solid fuel cell electrolytes. At the same time, because zirconium oxide powder is the main component of solid fuel cell electrolytes, its quality and performance have an important influence on the overall performance of the battery, and zirconium oxide will produce a reversible phase structure transformation when the temperature changes due to its martensitic phase transformation characteristics, which will cause corresponding volume changes in the process, making it difficult to make a dense film.
[0003] The ideal electrolyte for solid fuel cells is a dense pure oxygen ion conductor, which is required to have high oxygen ion conductivity and as low electronic conductivity as possible, and maintain good physical, chemical and structural stability in both reducing and oxidizing atmospheres. Doping zirconia with suitable oxides as stabilizers to form solid solutions and complexes with zirconia and thus change the internal structure of the crystal is an effective means to improve unstable zirconia. At present, most solid fuel cells use yttria-stabilized zirconia as electrolyte materials, but yttria has limited effects on the oxygen ion conductivity and density of zirconia; and different types and contents of doped oxides have very different effects on the performance of zirconia powder, and the corresponding preparation process is also a key factor affecting the performance of the obtained zirconia powder; based on this, the study of preparing a multi-component composite doped zirconia powder is of great significance for the preparation of high-performance solid fuel cells. Summary of the invention
[0004] In view of the problems raised in the background technology, the purpose of the present invention is to provide a multi-component composite doped zirconium oxide powder for solid fuel cells and a preparation method thereof. The method of the present invention optimizes the type, amount and corresponding calcination process of the composite doped oxide system of the zirconium oxide powder to prepare a high-quality zirconium oxide powder with high conductivity and good stability, which meets the high performance requirements of various solid fuel cell electrolytes.
[0005] In order to achieve the above object, the present invention specifically adopts the following technical solutions: The present invention provides a method for preparing a multi-component composite doped zirconium oxide powder for a solid fuel cell, comprising the following steps: Step 1): zirconium oxychloride is mixed with a stabilizer soluble salt and a composite additive, and water is added while heating and hydrolyzing to obtain a mixed solution, which is continuously stirred and the pH is adjusted, and then filtered, washed and dried to obtain a mixed powder A for standby use; the stabilizer soluble salt is scandium chloride or scandium nitrate, and the composite additive is composed of cerium salt, aluminum salt, bismuth salt and gadolinium salt; Step 2): separately taking zirconium oxychloride and mixing with carbon nanotubes and organic frameworks, adding them to an ethanol solution and stirring evenly, adjusting the pH of the ethanol mixture and heating and standing, then vacuum filtering and washing, drying the obtained mixture to obtain a modified mixture, mixing and grinding the obtained modified mixture with yttrium oxide, calcium oxide and magnesium oxide to obtain a mixed powder B for use; Step 3): Grind and mix the mixed powder A and the mixed powder B, calcine at a high temperature of 1000-1080°C, then cool to 740-820°C for temperature-controlled calcination, and finally wet-grind and spray-dry to obtain multi-component composite-doped nano zirconium oxide powder.
[0006] Furthermore, in step 1), the addition amount of each raw material is 86.8%-89.0% of zirconium oxychloride, 5.6%-9.4% of stabilizer soluble salt, 1.45%-1.94% of cerium salt, 1.0%-1.2% of aluminum salt, 1.42%-1.90% of bismuth salt, and 0.03%-0.10% of gadolinium salt, based on molar percentage; the cerium salt, aluminum salt, bismuth salt, and gadolinium salt are chlorides or nitrates.
[0007] Furthermore, in step 1), the temperature of heating and hydrolysis is 50-65° C., and the pH of the mixed solution obtained by hydrolysis is adjusted to 8.0-8.8 by adding ammonia water dropwise.
[0008] Furthermore, in step 2), the mass ratio of zirconium oxychloride, carbon nanotubes and organic framework is 100:(4-8):(0.3-0.6), and the organic framework is preferably a zirconium-based metal organic framework UIO-66Zr.
[0009] Furthermore, in step 2), the ethanol mixture is adjusted to a pH of 10-11 by adding sodium hydroxide dropwise, and then kept at 50-65° C. for 8-12 h.
[0010] Furthermore, in step 2), the addition amounts of zirconium oxychloride, yttrium oxide, calcium oxide and magnesium oxide are as follows: zirconium oxychloride 87.2%-90.5%, yttrium oxide 6.60%-14.2%, calcium oxide 1.15%-1.70% and magnesium oxide 0.80%-1.25% by mole percentage.
[0011] Furthermore, in step 3), the mass ratio of mixed powder A to mixed powder B is (6.5-8):(2-3.5).
[0012] Furthermore, in step 3), the heating rate of high temperature calcination is controlled at 2-4°C / min, and the high temperature calcination time is 2-3h; the cooling rate of subsequent cooling is controlled at 8-10°C / min, and the temperature-controlled calcination time after cooling is 10-12h.
[0013] The volume effect caused by the phase structure transformation of zirconium oxide powder is mainly solved by adding metal ion oxides (such as Y 2 O 3 ) as a stabilizer. With the gradual improvement of people's requirements for the performance of solid fuel cells, conventional single stabilizer doped zirconium oxide powder can no longer meet the use requirements, and the addition of oxides of different types and contents has a significant difference in the effect on zirconium oxide powder. Therefore, multi-component composite doping has become a better choice for preparing zirconium oxide powder for solid fuel cells with more perfect performance. But at the same time, different additives will cause a significant reduction in interfacial compatibility due to differences in properties and mismatch with the lattice structure of zirconium oxide, thereby affecting the overall stability and other properties of zirconium oxide powder. The present invention preferably uses oxide types and molar ratios. On the one hand, scandium is used as the main stabilizer, and cerium salts, aluminum salts, bismuth salts, and gadolinium salts are used as composite additives to construct an initial doping system, which is heated and hydrolyzed with zirconium oxychloride; on the other hand, carbon nanotubes and organic frameworks are first used to modify zirconium oxychloride, and then the modified mixture is mixed with yttrium oxide, calcium oxide, and magnesium oxide as a combined doping system; after the two doping systems are mixed in proportion, a multi-component composite doped zirconium oxide powder is obtained through a two-step calcination process. The composite doping system selected by the present invention can effectively inhibit the high-temperature phase transformation of zirconia, stabilize the cubic phase and avoid the appearance of the low-temperature phase, maintain its structural integrity and stability, promote densification, and help improve the electrical conductivity; the synergistic modification of carbon nanotubes and organic frameworks can promote the uniform dispersion of doped oxides and zirconia powders, prevent agglomeration, and cooperate with the two-step calcination process of the present invention to significantly improve the compatibility between the zirconia powder doping systems, further improving the electrical conductivity and stability.
[0014] The beneficial effects of the present invention are: The present invention overcomes the limitations of existing single-doped zirconia powders and prepares a multi-component composite-doped zirconia powder. The nano zirconia powder has high oxygen ion conductivity and can maintain excellent stability in a high-temperature environment, meeting the high-performance requirements of various solid fuel cell electrolytes and having good market competitiveness. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0016] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0017] Example 1 A method for preparing multi-component composite doped zirconium oxide powder for solid fuel cells comprises the following steps: 1. Take ZrOCl by mole percentage 2 8H 2 O 87.84mol%, ScCl 3 7.7mol%Ce(NO 3 ) 3 1.68mol%AlCl 3 1.1mol%BiCl 3 1.62mol%Gd(NO 3 ) 3 0.06mol%. The above raw materials were added with 3 times the mass of water, and the mixture was heated to 55°C for hydrolysis to obtain a mixed solution. Ammonia water was added dropwise to the mixed solution under vigorous stirring to adjust the pH to 8.4. After filtering, deionized water was added for washing, and further dried to obtain mixed powder A for use.
[0018] 2. Take ZrOCl by mole percentage 2 8H 2 O 89.0mol%, yttrium oxide 8.49mol%, calcium oxide 1.46mol%, magnesium oxide 1.05mol%; to ZrOCl 2 8H 2 5% of carbon nanotubes by weight and 0.5% of organic framework UIO-66Zr were added to the mixture, and the mixture was added to an ethanol solution (volume fraction 50%) with a weight that was 5 times the weight of the mixture and stirred evenly. Subsequently, a sodium hydroxide solution was added dropwise to adjust the pH to 10.5, and the mixture was heated to 55°C and kept standing for 10 h. After vacuum filtration, deionized water was added to wash the mixture, and the obtained mixture was dried to obtain a modified mixture. The obtained modified mixture was mixed and ground with yttrium oxide, calcium oxide, and magnesium oxide to obtain a mixed powder B for later use.
[0019] 3. Grind and mix the mixed powder A and mixed powder B in a mass ratio of 7.2:2.8, heat to 1060°C (heating rate 3°C / min) and calcine at high temperature for 2.5 h, then cool to 780°C (cooling rate 9°C / min) and continue to calcine at controlled temperature for 12 h. Add ethanol to the obtained product and ball mill (material-liquid ratio 3:1) to disperse it until D50 does not exceed 0.4 μm, and then spray dry it to obtain multi-component composite-doped nano-zirconia powder.
[0020] Example 2 A method for preparing multi-component composite doped zirconium oxide powder for solid fuel cells comprises the following steps: 1. Take ZrOCl by mole percentage 2 8H 2 O 86.84mol%ScCl 3 8.7mol%Ce(NO 3 ) 3 1.94mol%AlCl 3 1mol%BiCl 3 1.42mol%Gd(NO 3 ) 3 0.1mol%. Add 3 times the mass of water to the above raw materials and mix them. Heat to 50℃ for hydrolysis to obtain a hydrated zirconium oxide mixed solution. Add ammonia water dropwise to the mixed solution under vigorous stirring to adjust the pH to 8.8. After filtering, add deionized water for washing, and further dry to obtain mixed powder A for use.
[0021] 2. Take ZrOCl by mole percentage 2 8H 2 O 87.65mol%, yttrium oxide 10.4mol%, calcium oxide 1.15mol%, magnesium oxide 0.8mol%; to ZrOCl 2 8H 2 8% of carbon nanotubes by weight and 0.3% of organic framework UIO-66Zr were added to the mixture, and then added to an ethanol solution (volume fraction 50%) with a weight that is 5 times the weight of the mixture and stirred evenly. Subsequently, sodium hydroxide solution was added dropwise to adjust the pH to 10, and the mixture was heated to 50°C and kept standing for 8 h. After vacuum filtration, deionized water was added to wash the mixture, and the obtained mixture was dried to obtain a modified mixture. The obtained modified mixture was mixed and ground with yttrium oxide, calcium oxide, and magnesium oxide to obtain a mixed powder B for later use.
[0022] 3. Grind and mix the mixed powder A and mixed powder B in a mass ratio of 6.5:3.5, heat to 1020°C (heating rate 3°C / min) and calcine at high temperature for 2 h, then cool to 800°C (cooling rate 8°C / min) and continue to calcine at controlled temperature for 10 h. Add ethanol to the obtained product and ball mill (material-liquid ratio 3:1) to disperse it until D50 does not exceed 0.4 μm, and then spray dry it to obtain multi-component composite doped nano zirconium oxide powder.
[0023] Example 3 A method for preparing multi-component composite doped zirconium oxide powder for solid fuel cells comprises the following steps: 1. Take ZrOCl by mole percentage 2 8H 2 O 88.81mol%ScCl 3 6.61mol%Ce(NO 3 ) 3 1.45mol%AlCl 3 1.2mol%BiCl 3 1.9mol%Gd(NO 3 ) 3 0.03mol%. The above raw materials were added with 3 times the mass of water, and the mixture was heated to 60°C for hydrolysis to obtain a mixed solution. Ammonia water was added dropwise to the mixed solution under vigorous stirring to adjust the pH to 8.2. After filtering, deionized water was added for washing, and further dried to obtain mixed powder A for use.
[0024] 2. Take ZrOCl by mole percentage 2 8H 2 O 90.13mol%, yttrium oxide 6.92mol%, calcium oxide 1.7mol%, magnesium oxide 1.25mol%; to ZrOCl 2 8H 2 4% of carbon nanotubes by weight and 0.6% of organic framework UIO-66Zr were added to the mixture, and then added to an ethanol solution (volume fraction 50%) with a weight that is 5 times the weight of the mixture and stirred evenly. Subsequently, sodium hydroxide solution was added dropwise to adjust the pH to 11, and the mixture was heated to 60°C and kept standing for 12 h. After vacuum filtration, deionized water was added to wash the mixture, and the obtained mixture was dried to obtain a modified mixture. The obtained modified mixture was mixed and ground with yttrium oxide, calcium oxide, and magnesium oxide to obtain a mixed powder B for later use.
[0025] 3. Grind and mix the mixed powder A and mixed powder B in a mass ratio of 4:1, heat to 1080°C (heating rate 4°C / min) and calcine at high temperature for 3 h, then cool to 740°C (cooling rate 10°C / min) and continue to calcine at controlled temperature for 12 h. Add ethanol to the obtained product and ball mill (material-liquid ratio 3:1) to disperse it until D50 does not exceed 0.4 μm, and then spray dry it to obtain multi-component composite doped nano zirconium oxide powder.
[0026] Comparative Example 1 Refer to the step parameters of Example 1, except that in step 1, ZrOCl is taken by molar percentage 2 8H 2 O87.84mol%ScCl 3 9.38mol%Ce(NO 3 ) 3 1.68mol%AlCl 3 1.1 mol% was used as the raw material system for preparing mixed powder A.
[0027] Comparative Example 2 Refer to the step parameters of Example 1, except that in step 1, ZrOCl is taken by molar percentage 2 8H 2 O87.84mol%ScCl 3 7.7mol%Ce(NO 3 ) 3 1.68mol%YCl 3 1.16mol%BiCl 3 1.62 mol% is used as the raw material system for preparing mixed powder A.
[0028] Comparative Example 3 Refer to the step parameters of Example 1, except that in step 2, ZrOCl 2 8H 2 Only 5.5% of the mass of carbon nanotubes was added to O to prepare modified zirconia, without adding an organic framework.
[0029] Comparative Example 4 Refer to the step parameters of Example 1, except that in step 2, ZrOCl 2 8H 2 Only 0.5% of the mass of the organic framework UIO-66Zr was added to O to prepare the modified zirconia, without adding carbon nanotubes.
[0030] Comparative Example 5 The step parameters of Example 1 are referred to, except that the mixed powder A prepared in step 1 of Example 1 is directly used as the raw material, and the zirconium oxide powder is obtained after calcination in step 3.
[0031] Comparative Example 6 The step parameters are as in Example 1, except that in step 3, the temperature is directly heated to 1060° C. (heating rate 3° C. / min) and the high temperature calcination is continued for 6 h.
[0032] Test example The powders prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-6 were tested (the specific surface area was measured using an SSA-3500 fully automatic specific surface area analyzer; D 50 The results are shown in Table 1.
[0033] Table 1 Powder specific surface area and D 50 Test results
[0034] The powders prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-6 were dry pressed and sintered at 1300°C for 3 h, and then cut into strips (4mm×4mm×50mm). The three-point bending strength was repeatedly measured by a tensile testing machine to obtain an average value. The powders were mixed with a solvent (xylene / ethanol = 1:1, v / v) at a mass ratio of 4:1, and ball milled to obtain a slurry. Then, 8% of the mass of polyvinyl butyral, 3.9% of butyl benzyl phthalate, and 0.1% of cyclohexanone were added to the obtained slurry, and the mixture was ball milled to obtain a casting slurry. After degassing, the film was formed and demolded on a casting machine to form a film (0.5mm). Finally, the dielectric sheet was obtained after high-temperature sintering (heating from room temperature to 1350°C at 2°C / min, keeping the temperature for 5 h, and then cooling to room temperature at 2°C / min). The conductivity at different temperatures was tested respectively.
[0035] The results are shown in Table 2.
[0036] Table 2 Test results of sintered body and dielectric sheet performance
[0037] According to the test data in Table 1, the multi-component composite doped nano-zirconia powder sintered body of the present invention has high strength, and its three-point bending strength exceeds 600 MPa; at the same time, the prepared dielectric sheet has high conductivity and excellent high-temperature stability, which is greatly improved compared with powders made from other doped oxide combinations. The nano-zirconia powder of the present invention has high oxygen ion conductivity and excellent stability, can meet the high performance requirements of various solid fuel cell electrolytes, and has good market competitiveness.
[0038] The embodiments described above only express several preferred embodiments of the present invention, and the descriptions thereof are relatively specific and detailed, but are not intended to limit the present invention. It should be noted that for those skilled in the art, the present invention may also have various changes and modifications, and any modifications, equivalent substitutions, improvements, etc. made within the concept and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing multi-component composite doped zirconium oxide powder for solid fuel cells, characterized in that: The steps include: Step 1): zirconium oxychloride is mixed with a stabilizer soluble salt and a composite additive, and water is added while heating and hydrolyzing to obtain a mixed solution, which is continuously stirred and the pH is adjusted, and then filtered, washed and dried to obtain a mixed powder A for standby use; the stabilizer soluble salt is scandium chloride or scandium nitrate, and the composite additive is composed of cerium salt, aluminum salt, bismuth salt and gadolinium salt; Step 2): separately taking zirconium oxychloride and mixing with carbon nanotubes and organic frameworks, adding them to an ethanol solution and stirring evenly, adjusting the pH of the ethanol mixture and heating and standing, then vacuum filtering and washing, drying the obtained mixture to obtain a modified mixture, mixing and grinding the obtained modified mixture with yttrium oxide, calcium oxide and magnesium oxide to obtain a mixed powder B for use; Step 3): Grind and mix the mixed powder A and the mixed powder B, calcine at a high temperature of 1000-1080°C, then cool to 740-820°C for temperature-controlled calcination, and finally wet-grind and spray-dry to obtain multi-component composite-doped nano zirconium oxide powder.
2. The method for preparing the multi-component composite doped zirconium oxide powder for solid fuel cells according to claim 1, characterized in that: In step 1), the addition amount of each raw material is 86.8%-89.0% of zirconium oxychloride, 5.6%-9.4% of stabilizer soluble salt, 1.45%-1.94% of cerium salt, 1.0%-1.2% of aluminum salt, 1.42%-1.90% of bismuth salt, and 0.03%-0.10% of gadolinium salt, based on molar percentage; the cerium salt, aluminum salt, bismuth salt, and gadolinium salt are chlorides or nitrates.
3. The method for preparing multi-component composite doped zirconium oxide powder for solid fuel cells according to claim 1, characterized in that: The temperature of heating and hydrolysis in step 1) is 50-65° C., and the pH of the mixed solution obtained by hydrolysis is adjusted to 8.0-8.8 by adding ammonia water dropwise.
4. The method for preparing multi-component composite doped zirconium oxide powder for solid fuel cells according to claim 1, characterized in that: In step 2), the mass ratio of zirconium oxychloride, carbon nanotubes and organic framework is 100:(4-8):(0.3-0.6), and the organic framework is a zirconium-based metal organic framework UIO-66Zr.
5. The method for preparing multi-component composite doped zirconium oxide powder for solid fuel cells according to claim 1, characterized in that: In step 2), the ethanol mixture is adjusted to a pH of 10-11 by adding sodium hydroxide dropwise, and then kept at 50-65° C. for 8-12 h.
6. The method for preparing multi-component composite doped zirconium oxide powder for solid fuel cells according to claim 1, characterized in that: In step 2), the addition amounts of zirconium oxychloride, yttrium oxide, calcium oxide and magnesium oxide are as follows: 87.2%-90.5% of zirconium oxychloride, 6.60%-14.2% of yttrium oxide, 1.15%-1.70% of calcium oxide and 0.80%-1.25% of magnesium oxide, based on molar percentage.
7. The method for preparing multi-component composite doped zirconium oxide powder for solid fuel cells according to claim 1, characterized in that: In step 3), the mass ratio of mixed powder A to mixed powder B is (6.5-8):(2-3.5).
8. The method for preparing multi-component composite doped zirconium oxide powder for solid fuel cells according to claim 1, characterized in that: In step 3), the heating rate of medium-high temperature calcination is controlled at 2-4°C / min, and the high temperature calcination time is 2-3 h; the cooling rate of subsequent cooling is controlled at 8-10°C / min, and the temperature-controlled calcination time after cooling is 10-12 h.
9. A multi-component composite doped zirconium oxide powder for solid fuel cells prepared by the method according to any one of claims 1 to 8.
Citation Information
Cited By
Preparation method of multi-component oxide powder
CN121269734A